Molecular characterization of cross-kingdom RNA interference in Botrytis cinerea by tomato small RNAs - Qin, Si; Veloso, Javier; Puccetti, Guido; van Kan, Jan A. L. (Frontiers in Plant Science, 2023)
Previous studies have suggested that plants can modulate gene expression in pathogenic fungi by producing small RNAs (sRNAs) that can be translocated into the fungus and mediate gene silencing, which may interfere with the infection mechanism of the intruder. We sequenced sRNAs in early phases of the Solanum lycopersicum (tomato)-Botrytis cinerea interaction and examined the potential of plant sRNAs to silence their predicted mRNA targets in the fungus. Almost a million unique plant sRNAs were identified that could potentially target 97% of all fungal genes. We selected three fungal genes for detailed qRT-PCR analysis of the correlation between the abundance of specific plant sRNAs and their target mRNAs in the fungus. The fungal Bcspl1 gene, which had been reported to be important for the fungal virulence, showed transient down-regulation around 20 hours post inoculation and contained a unique target site for a single plant sRNA that was present at high levels. In order to study the functionality of this plant sRNA in reducing the Bcspl1 transcript level, we generated a fungal mutant that contained a 5 nucleotide substitution that would abolish the interaction between the transcript and the sRNA without changing the encoded protein sequence. The level of the mutant Bcspl1 transcript showed a transient decrease similar to wild type transcript, indicating that the tomato sRNA was not responsible for the downregulation of the Bcspl1 transcript. The virulence of the Bcspl1 target site mutant was identical to the wild type fungus.